2017
DOI: 10.1080/15384101.2017.1295182
|View full text |Cite
|
Sign up to set email alerts
|

Bcl-2 delays cell cycle through mitochondrial ATP and ROS

Abstract: Bcl-2 inhibits cell proliferation by delaying G/G to S phase entry. We tested the hypothesis that Bcl-2 regulates S phase entry through mitochondrial pathways. Existing evidence indicates mitochondrial adenosine tri-phosphate (ATP) and reactive oxygen species (ROS) are important signals in cell survival and cell death, however, the molecular details of how these 2 processes are linked remain unknown. In this study, 2 cell lines stably expressing Bcl-2, 3T3Bcl-2 and C3HBcl-2, and vector-alone PB controls were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 34 publications
3
20
0
Order By: Relevance
“…COX-1 knockdown in the present study induced caspase-dependent apoptosis with upregulation of cytosolic cytochrome c, caspase-9 and -3 activation, and PARP cleavage, along with downregulation of mitochondria cytochrome c, which indicated that cytochrome c leaks from the mitochondria to the cytosol. In addition, Bcl-2 family members are key factors in mitochondrial function, cell cycle and apoptosis (23,24). In the present study, it was also revealed that downregulation of COX-1 in CRC cells significantly decreased anti-apoptotic Bcl-2 expression and increased pro-apoptotic Bax expression, with deleterious mitochondrial function.…”
Section: Discussionsupporting
confidence: 64%
“…COX-1 knockdown in the present study induced caspase-dependent apoptosis with upregulation of cytosolic cytochrome c, caspase-9 and -3 activation, and PARP cleavage, along with downregulation of mitochondria cytochrome c, which indicated that cytochrome c leaks from the mitochondria to the cytosol. In addition, Bcl-2 family members are key factors in mitochondrial function, cell cycle and apoptosis (23,24). In the present study, it was also revealed that downregulation of COX-1 in CRC cells significantly decreased anti-apoptotic Bcl-2 expression and increased pro-apoptotic Bax expression, with deleterious mitochondrial function.…”
Section: Discussionsupporting
confidence: 64%
“…38,39 Consequently, targeting ROS has been considered a promising strategy for anti-tumor therapy, since it can stimulate or inhibit different cell signaling pathways to induce apoptosis and autophagy thereby inhibit tumor growth. 40,41 Additionally, high levels of ROS can induce cell cycle arrest. In the present study, PPVI-induced cell death paralleled the levels of ROS.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with the fact that Bcl-2’s anti-tumor function was activated only in G 0 /G 1 stage after serum starvation but not in normal growing status (Janumyan et al, 2008). Taken together, these results strongly indicate that ROS might play a role in Bcl-2’s cell cycle function (Du et al, 2017). Mitochondrial OXPHOS impinges on many cellular functions, including energy allocation and programmed cell death.…”
Section: Discussionmentioning
confidence: 66%
“…Cells transfected with the empty vector served as the control (referred to as 3T3PB in this paper). We have reported that PGC-1α inhibits the cell cycle progress, and Bcl-2 exerts its anti-tumor function by delay cell cycle progress only at the G 0 /G 1 stage (Fu et al, 2016; Du et al, 2017; Janumyan et al, 2008). Therefore, here, we first synchronize cells at the G0/G1 stage by serum starvation, then compare PGC-1α expression in 3T3Bcl-2 cells with 3T3PB cells.…”
Section: Resultsmentioning
confidence: 99%